Consumers in CARICOM (Caribbean Community Secretariat GeorgetownGY, 2012)
Provides a guide to CARICOM and non-CARICOM consumers in relation to avenues for obtaining redress as they travel to member territories of the Community, or acquire goods and services online from suppliers operating outside thier own country.
Available in print and CDRom versions